Case Report: Prepubertal-type testicular teratoma with local metastasis in a postpubertal patient - Ghirardelli Smith, Olivia C.; Tsai, Alexander K.; Zhong, Minghao; Dejban, Pegah; Nelson, Andrew C.; Dolan, Michelle; Antonarakis, Emmanuel S.; Murugan, Paari (Frontiers in Oncology, 2025)
IntroductionWe report for the first time a case of a postpubertal patient presenting with a metastatic prepubertal-type testicular teratoma.Case discussionA 29-year-old male with a history of corrected unilateral cryptorchidism presented with progressive bilateral lower extremity edema. Imaging revealed an inferior vena cava thrombus associated with a complex mass. A left testicular ultrasound identified a solid lesion suggestive of a germ cell tumor, leading to a left radical orchiectomy, which revealed a mature pure teratoma with no evidence of germ cell neoplasia in situ (GCNIS). Excision of the retroperitoneal mass confirmed the presence of mature teratomatous elements without evidence of non-teratomatous germ cell tumor elements or cytological atypia. Fluorescence in situ hybridization (FISH) showed no evidence of gain of 12p, and next-generation sequencing showed no alterations in genes known to be associated with GCT.ConclusionThis case illustrates that pure mature teratomas lacking chromosome 12p abnormalities, GCNIS, and other dysgenetic features, occurring in postpubertal males, cannot invariably be classified into the benign prepubertal-type teratoma category. Contrary to current paradigm, in rare cases these may represent tumors with metastatic potential.